Lesiones en cavidad oral en pacientes con VIH en un estado del sur de México - Chorley-Sánchez, Josymar (2019)
Objective: To determine the frequency of lesions of the oral cavity in people with HIV who are treated in the medical unit "Ambulatory Center for the prevention and care in AIDS and Sexually Transmitted Infections" (CAPASITS) of the city of Tuxtla Gutiérrez, Chiapas; Mexico. Methods: An observational, cross-sectional and prospective study was conducted in patients with a recent diagnosis of HIV, which included oral clinical review. Results: We included 58 patients diagnosed with HIV infection who were attended in the center in the period from June 2016 to March 2017, 75.9% were men, with an average of 31.6 years, 55.2% of them admitted heterosexuality and a primary level education (42.9%). The group of oral pathologies most frequently found were mycotic (89.7%), followed by bacterial (72.4%) and viral (65.5%), the most frequent lesions were pseudomembranous candidiasis (98.1%), hairy leukoplakia (60.3%) and gingival erythema (56.9%). Conclusions: 77.6% of the patients presented from two to four lesions, so that lesions in the oral cavity can be indicative of the level of the immune status of an individual, therefore, the dentist may be the first health professional to suspect the presence of HIV infection.